Perancangan Aplikasi Pemesanan Travel Antar Kota Di Sumatera Barat Berbasis Android - Cindy Klaudya Putri; Dwiny Meidelfi; Aldo Erianda (Indonesian Society of Applied Science, 2020)
The development in the field of technology is currently growing rapidly, one of the technological developments at this time is the internet. Then what is obtained by using the internet can also be utilized in the field of transportation, namely by making an Android mobile-based travel ticket booking information system using a smartphone. Travel is a type of transportation service that serves passengers with a door to door or pickup system at the booking address, then delivered to the destination address. However, the process of booking travel tickets today is still done traditionally by coming to the counter or branch office of travel so it takes a lot of time and is inefficient, and there are also several other ways to call a travel agent, sometimes such methods are not effective because of the occurrence of a pile of tickets without accurate data. Therefore this study aims to facilitate travel passengers in searching or booking Travel tickets in the West Sumatra Region by designing an Android mobile application. Apart from that in providing location information to the drivers of the traveling fleet to pick up passengers at certain locations by using Google Maps, and application features such as travel schedules, ticket checks, ticket reservations, and account registration.